Avaliação do comportamento estrutural de ligações viga-coluna parafusadas com cantoneiras duplas na alma - Silva, Felipe Leite (2016)
When modeling steel structures, some connections are considered flexible. One of them is double angle with bolts in both sides of the elements that are connected. This hypothesis simplifies the whole structural analysis, but in some cases bending moments could be transmitted from beams to columns with that kind of connections. The issue of this work is to estimate rotational stiffness for a double-web angle connection with bolts. For this objective, numerical and experimental simulations were developed, first with a simple supported beam and a pinned beam has a reference, and after with beam with double-angle connections. This research adds significant results to others in the references, because both modeling, experimental and numerical, were developed with the beam with both ends considered. Results shows an 18 % of bending moment reduction compared to the model of simple-supported beam. Additionally, that kind of connection could be classified as semi-rigid by the Brazilian standard ABNT NBR 8800.